HANNAH ARENDT: THE APPEARANCES OF ESTRANGEMENT - Jerome Kohn (Cadernos Arendt, 2022)
The times we live in are perverse in diverse ways, not only, but also not least, politically. In 2016 we elected a president whose appear- ance in public is avaricious, destructive, deceitful, predatory, and incoherent. It would be hard to imagine a Balzac or Dickens depict- ing a fictional character more brazenly self-absorbed than this braggart who has no hesitation in calling himself “like, really smart.” Was it Trump alone who visualized himself presiding over—liter- ally, sitting before — more than 300 million Americans? According to him, that qualifies “as not smart, but genius.” But what are the odds, one wonders, of this vulgarian stinging and awakening us, the people, from the political narcolepsy we’ve dreamed in for the past 50 years?